Type A asparagine synthetase in the zoonotic Cryptosporidium parvum (CpAsnA): Biochemical features and potential as a novel therapeutic target - Zongzhen Zhai; Peng Jiang; Dongqiang Wang; Tao Chen; Jigang Yin; Guan Zhu (International Journal for Parasitology: Drugs and Drug Resistance)
Cryptosporidium parvum is an intestinal protozoan parasite, the causative agent of the diarrheal cryptosporidiosis in humans and animals for which fully effective treatments are yet unavailable. The C. parvum genome encodes highly streamlined metabolic pathways, lacking enzymes to synthesize any amino acids de novo. However, it possesses a standalone type A asparagine synthetase (CpAsnA) that catalyzes the ammonia/ATP-dependent synthesis of asparagine from aspartate. Here, we expressed recombinant CpAsnA and characterized its enzyme functional parameters towards aspartate. We screened 5000 bioactive compounds using a thermal shift assay (TSA) and identified 31 hits showing high binding affinity to CpAsnA. Four of the 31 TSA hits exhibited lower micromolar activity against CpAsnA enzyme activity, including XD14, SB225002, histone acetyltransferase inhibitor II (HATi-II) and tolcapone. Among the four CpAsnA inhibitors, three displayed lower micromolar in vitro efficacy against the growth of C. parvum in vitro with satisfactory selectivity indices as primary antiparasitic hits. Our data suggest that CpAsnA merits further investigation as a potential drug target in the parasite.